Factors, Impacts, and Prevention Strategies of Violence Against Nurses: A Qualitative Study - Heryyanoor, Heryyanoor; Hardiyanti, Diana; Pertiwi, Melinda Restu; Febriana, Annisa; Safariansyah, Hari (JURNAL CITRA KEPERAWATAN, 2025)
Violence against nurses remains a significant challenge affecting their physical safety, psychological well-being, and professional performance. This study explored the factors contributing to violent behavior against nurses, their diverse impacts, and effective prevention strategies. A qualitative design was used to collect data from thirteen participants through interviews and to analyze them thematically. The study findings revealed that internal factors such as high workload, ineffective communication, and staff attitudes, alongside external factors including patient and family expectations, emotional states, and socio-cultural influences, contributed to violent incidents. The impacts identified included physical injury, psychological trauma, decreased motivation, and compromised quality of care. Participants highlighted prevention strategies involving positive nurse attitudes, patient and family education, effective communication, precise reporting mechanisms, institutional support, psychosocial support, and use of digital technology. The study concluded that addressing violent behavior against nurses requires a comprehensive and multidimensional approach that integrates personal, organizational, and technological interventions. It is recommended that nursing practice prioritize therapeutic communication and empathy, supported by strong policies and psychosocial resources to improve nurse safety and quality of care.